ON THE CREATION OF NATIONAL DIVISIONS IN THE COMPOSITION OF THE RED ARMY IN THE UNION AND AUTONOMOUS REPUBLICS OF THE USSR IN DECEMBER OF 1941 - Ubusaev, V B; Sarapova, E P (History, Archeology and Ethnography of the Caucasus, 2016)
This work is dedicated to the establishment in the early months of World War II (November-December 1941) in the number of union and autonomous republics several dozens of national military forces in the Red Army. Hundreds of thousands of workers continuously supported a broad patriotic movement and collected people’s funds for creation of tank columns, combat aircraft, armored trains, artillery battery and even submarines. In addition, rear workers sent to the front a huge number of gifts to Soviet soldiers. Among the valuable patriotic deeds of the people was, of course, the creation of national military units - cavalry divisions, brigades, regiments, etc. Established in the winter 1941, the 110-th separate Kalmyk Cavalry Division participated in battles on the Don, in the liberation from the enemy territory of the North Caucasus.